Learning Together? Experiences on a China–U.K. Articulation Program in Engineering. (July 2014) - Hou, Junxia; McDowell, Liz
This article reports some of the findings of a longitudinal ethnographic research study on the intercultural transition experiences of 50 engineering students in a China–U.K. articulation program. It focuses on the interaction between these students and the U.K.-based cohort, mainly home students. The findings indicate that lack of suitable interventions at the initial stage, the competition for insufficient resources, double-language barriers, and different questioning behaviors led the Chinese and U.K. students to self-categorize themselves into "us" and "them." The separation has a negative impact on peer learning. This research suggests that integration in the class can be promoted through developing a low-stakes learning environment, enhancing intercultural competence and developing a common in-group identity as engineering students on the same program.